Keo, Chetra (audio interview #2 of 5) - Keo, Chetra; Pierce, Mark, interviewer
<>INTERVIEW DESCRIPTION<> - This is the second of five interviews conducted over a three month period with Chetra Keo, a friend of the interviewer. The interview was conducted in Keo's room, late at night. Despite both interviewer and narrator being tired, once the interview got going, both sprung to life. The purpose of this interviews was to clarify and elicit more details on some of the topics discussed in the first interview. The interviewer noted that his questions lacked the clarity of those asked in the first interview; that at times he didn't know how to phrase a particular question. Unfortunately, he notes that he didn't time the ending of each tape well, cutting off the narrator in the middle of a sentence. It should be noted that the segments in this interview tend to be rather long. 9/1/1989